Designing Coastal Adaptation Strategies to Tackle Sea Level Rise - Bongarts Lebbe, Théophile; Rey-Valette, Hélène; Chaumillon, Éric; Camus, Guigone; Almar, Rafael; Cazenave, Anny; Claudet, Joachim; Rocle, Nicolas; Meur-Férec, Catherine; Viard, Frédérique; Mercier, Denis; Dupuy, Christine; et al. (Frontiers in Marine Science, 2021)
Faced with sea level rise and the intensification of extreme events, human populations living on the coasts are developing responses to address local situations. A synthesis of the literature on responses to coastal adaptation allows us to highlight different adaptation strategies. Here, we analyze these strategies according to the complexity of their implementation, both institutionally and technically. First, we distinguish two opposing paradigms – fighting against rising sea levels or adapting to new climatic conditions; and second, we observe the level of integrated management of the strategies. This typology allows a distinction between four archetypes with the most commonly associated governance modalities for each. We then underline the need for hybrid approaches and adaptation trajectories over time to take into account local socio-cultural, geographical, and climatic conditions as well as to integrate stakeholders in the design and implementation of responses. We show that dynamic and participatory policies can foster collective learning processes and enable the evolution of social values and behaviors. Finally, adaptation policies rely on knowledge and participatory engagement, multi-scalar governance, policy monitoring, and territorial solidarity. These conditions are especially relevant for densely populated areas that will be confronted with sea level rise, thus for coastal cities in particular.